Primary breast osteosarcoma: A case report highlighting the importance of radiologic-pathologic correlation - Bailee Lichter, MS; Madison Landon, MS; DesiRae Muirhead, MD; Daniel Fetzer, MD (Radiology Case Reports)
Osteosarcoma of primary breast origin is a rare form of malignancy. Imaging findings are nonspecific and often overlap with other differential considerations reinforcing the importance of radiologic-pathologic correlation for an accurate diagnosis. This case report details the clinical presentation, imaging findings, histopathological features, and therapeutic approach that transpired to diagnose and treat this rare malignancy.